1985
DOI: 10.1177/0011128785031001007
|View full text |Cite
|
Sign up to set email alerts
|

Is Violent Crime Intraracial?

Abstract: The commonly accepted view that violent crime is intraracial as opposed to interracial is reexamined. Victim survey data on perceived race of offender are used to suggest that the issue of intraracial versus interracial crime should be examined from four perspectives: white offender's choice of victim (e.g., white or black); black offender's choice of victim; white victim's perception of race of offender; and black victim's perception of race of offender. A Detailed analysis of victimization survey data indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…Because defendants with documented mental health conditions in our sample were more likely to be White and more likely to have White victims, our results appear consistent with prior research that suggests violent offenders tend to perpetrate crimes against victims who are members of the same racial group (Harrell, 2007;Wilbanks, 1985). Contrary to prior research suggests that capital trial outcomes may be affected by the race characteristics of both the defendant and victim (Keil and Vito, 1995;Thomson, 1997;Williams et al, 2007), our findings are consistent with the findings reported by .…”
Section: Discussionsupporting
confidence: 87%
“…Because defendants with documented mental health conditions in our sample were more likely to be White and more likely to have White victims, our results appear consistent with prior research that suggests violent offenders tend to perpetrate crimes against victims who are members of the same racial group (Harrell, 2007;Wilbanks, 1985). Contrary to prior research suggests that capital trial outcomes may be affected by the race characteristics of both the defendant and victim (Keil and Vito, 1995;Thomson, 1997;Williams et al, 2007), our findings are consistent with the findings reported by .…”
Section: Discussionsupporting
confidence: 87%
“…It was previously shown in Model 2 that racial segregation had a significant negative effect on the White-on-Black crime rate. One possible reason for the failure to detect a significant negative effect of racial segregation in the Black-on-White crime rate equation was that Black offenders were more apt than White offenders to venture out of their neighborhoods in order to victimize more lucrative targets (LaFree, 1982;Wilbanks, 1985). If this position has merit, then, racial segregation would be expected to play less of a role in explaining Black-on-White crime than White-on-Black crime.…”
Section: Regression Resultsmentioning
confidence: 99%
“…Several empirical studies buttress the view that racial animosity is a precipitating factor in the occurrence of black-on-white crime. Using national victimization data, Wilbanks (1985) found evidence that although most crime tends to be intraracial, black offenders are much more prone to select whites to rob, rape, and assault. He advances the possibility that this finding may be the result of black offenders ".…”
Section: Racial Animosity Theorymentioning
confidence: 99%
“…Other reasons besides racial heterogeneity cast doubt on the role of racial animosity in engendering black-on-white crime. For example, if whites are more lucrative targets for robberies and burglaries because of their higher incomes, then the greater incidence of black-on-white crime might be entirely explicated by dissimilarities in the socioeconomic standing of whites relative to blacks (Wadsworth and Kubrin, 2004;Wilbanks, 1985). This same logic of target attractiveness is also applicable to a nonmonetary crime, such as rape.…”
Section: Heterogeneity Theorymentioning
confidence: 99%